2013
DOI: 10.1200/jco.2012.43.1882
|View full text |Cite
|
Sign up to set email alerts
|

Germline BRCA Mutations Are Associated With Higher Risk of Nodal Involvement, Distant Metastasis, and Poor Survival Outcomes in Prostate Cancer

Abstract: A B S T R A C T PurposeTo analyze the baseline clinicopathologic characteristics of prostate tumors with germline BRCA1 and BRCA2 (BRCA1/2) mutations and the prognostic value of those mutations on prostate cancer (PCa) outcomes. Patients and MethodsThis study analyzed the tumor features and outcomes of 2,019 patients with PCa (18 BRCA1 carriers, 61 BRCA2 carriers, and 1,940 noncarriers). The Kaplan-Meier method and Cox regression analysis were used to evaluate the associations between BRCA1/2 status and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
516
4
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 707 publications
(591 citation statements)
references
References 38 publications
36
516
4
11
Order By: Relevance
“…11 Indeed, Castro and colleagues analyzed the clinicpathological characteristics of prostate cancers in BRCA1 and BRCA2 carriers and found carriers more frequently had high Gleason scores (8 or above), T3/4 stage, nodal involvement, metastases at diagnosis, and found that cause specific survival was shorter compared to non-carriers. 12 Other similar studies corroborate these findings. [13][14][15][16] Until recently, reports on the screening outcomes of male BRCA1/2 carriers have been scarce and often limited to specific founder mutations studied in a select population.…”
Section: E783supporting
confidence: 55%
“…11 Indeed, Castro and colleagues analyzed the clinicpathological characteristics of prostate cancers in BRCA1 and BRCA2 carriers and found carriers more frequently had high Gleason scores (8 or above), T3/4 stage, nodal involvement, metastases at diagnosis, and found that cause specific survival was shorter compared to non-carriers. 12 Other similar studies corroborate these findings. [13][14][15][16] Until recently, reports on the screening outcomes of male BRCA1/2 carriers have been scarce and often limited to specific founder mutations studied in a select population.…”
Section: E783supporting
confidence: 55%
“…However, there were no differences in median PSAV between carriers and noncarriers. Given the possibility that higher PSAV may associate with aggressive PrCa (D'Amico et al, 2004; D'Amico et al, 2005), we would expect BRCA2 carriers who are at risk of aggressive disease would exhibit higher PSAVs (Castro et al, 2013;Castro et al, 2015). BRCA2 carriers in this group may be too young to demonstrate this trend at this point of follow up.…”
Section: Discussionmentioning
confidence: 92%
“…This may help delineate PSAV among men diagnosed with PrCa with low PSA values (Carter et al, 1992; Kitagawa et al, 2014). A strength of this study is the unique patient cohort of men with a genetic predisposition to PrCa, in particular BRCA2 carriers who are predisposed to aggressive PrCas (Mitra et al, 2008;Narod et al, 2008;Castro et al, 2013;Castro et al, 2015). Within the group of BRCA2 carriers, PSAV proved predictive of any grade cancer, however, given the low number of cancers diagnosed overall it was not possible to assess whether PSAV was associated with high grade cancer and BRCA2 status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations